Diskursus Penafsiran Tentang Sedekah Kepada Non–Muslim di Kalangan Nahdlatul Ulama (NU) dan Muhammadiyah (MU) - Chairunnisyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This article explores the interpretation of almsgiving to non-Muslims according to the views of Nahdlatul Ulama (NU) and Muhammadiyah (MU). It is grounded in Surah Al-Baqarah, verse 272, which discusses the Prophet Muhammad's guidance against limiting almsgiving exclusively to Muslims and prohibits offering humanitarian assistance with the condition of converting to Islam. The study investigates how NU and MU understand almsgiving to non-Muslims, particularly focusing on their interpretation of the boundaries of almsgiving within the framework of Surah Al-Baqarah, verse 272, and their perspectives on its legal implications. The research uses a qualitative approach, gathering data through direct observations and interviews with NU leaders. The findings reveal that both NU and MU, based on their interpretations and scriptural evidence, concur that Allah SWT does not forbid acts of kindness toward non-Muslims who have established peaceful relations and do not engage in hostilities against Muslims. The verse also does not prevent fair treatment of them. The shared understanding between NU and MU is reflected in the similar meanings of Surah Al-Mumtahanah, verse 8, and Surah Al-Insan, verse 8, which underscore the principle of justice without religious bias. The conclusion is that almsgiving to non-Muslims is permissible. This study seeks to convey this perspective to the broader community and members of Islamic organizations, referencing relevant tafsir texts to provide a thorough explanation of the debate on almsgiving to non-Muslims and the interpretation of Surah Al-Baqarah, verse 272